Mapping the Scope and Maturity of Digital Technology Applications in Education: A Systematic Review - Fang, Yang (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
To comprehensively investigate the current state of digital education scenario applications in China, this study employs a Systematic Literature Review (SLR) approach to analyze the scope and maturity of digital technology applications in educational contexts between 2014 and 2024. By integrating educational scenarios with the “People–Process–Technology” (PPT) theory and the Capability Maturity Model Integration (CMMI), the study constructs a comprehensive “Educational Scenario–PPT Dimension–Maturity Model” framework to systematically analyze and reveal the developmental characteristics of digital transformation in education. The results indicate that: (1) the number of publications in the CNKI sample showed a fluctuating pattern from 2014 to 2021, with a resurgence after 2020 driven by policy initiatives and the COVID-19 pandemic; international research demonstrated a consistent growth trend, particularly accelerating after 2023 due to the influence of generative AI and large language models (LLMs); (2) research focus predominantly centered on teaching and learning scenarios, while areas such as home–school interaction, educational services, and educational practice remained underexplored; (3) higher education represented a research hotspot, whereas preschool and vocational education received relatively limited attention; and (4) most digital applications in educational scenarios were in the transition from “basic” to “mature” stages, with only a few achieving “optimized” or “leading” levels. This study provides a comprehensive analytical perspective for understanding digital transformation in education and offers insights for policy formulation, digital transformation practices, and future research directions.